(untitled) (Journal of Fatima Jinnah Medical University, 2018)
In our community pregnant population is exposed to harmful levels of pesticides in household and agricultural fields. Chlorpyrifos, an organophosphate pesticide, has been shown to be affecting brain development in various animal studies. Folic acid has a documented role in prevention of neural tube defects. Present study was designed to explore the teratogenic effects of chlorpyrifos on brain, in mice and to investigate whether folic acid has any role in prevention of these defects. Pregnant mice were divided into groups of 8 animals each, and were exposed to oral dose of 100 ug/gbw chlorpyrifos on GD 6 & 7(Group-A), 100 ug/gbw chlorpyrifos and/2ug/gbw Folic acid on GD 6 & 7 (Group-B), 100 ug/gbw chlorpyrifos on GD 6 &7 and 2 ug/gbw Folic acid on GD1 to 15(Group-C).Group D & E were plain control and folic acid control respectively. Fetuses were recovered on 15th day of gestation. Gross morphological and morphometeric study of recovered fetuses was done and histological study of brain region of embryos was also carried out. On morphological and morphometeric examination it was found that chlorpyrifos is teratogenic to mice fetuses in an oral dose of 100 ug/gbw when given on GD 6&7. It was embryotoxic, caused growth retardation and fetal anomalies of brain. Folic acid in a dose of 2 ug/gbw, when given at the time of chlorpyrifos exposure, (GD6&7) lead to reduction in the number of resorptions and frequency of anomalies. There was significant improvement in CR length and weight of fetuses on giving folic acid along with chlorpyrifos on GD 6&7. However the CR length and weight of fetuses given folic acid and chlorpyrifos were significantly less than the control. There was no additional benefit of giving folic acid in the same dose from GD1 to 15 on fetal weight and CR length but the improvement in the development of brain was more with folic acid use from GD1-15.